2022
DOI: 10.5604/01.3001.0016.0778
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Pedagogy Against the Background of a Holistic Vision of Pedagogy

Abstract: The aim of the article is an attempt to reflect on sexual pedagogy as a subdiscipline and an attempt to (o)draw the image of sexual pedagogy against the background of a holistic vision of pedagogy. Interest in this subject results from the marginalization of it in pedagogical discourse. The article will describe the category of normativity as an element needed in sexual pedagogy and clues for the education of tomorrow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ratkowska-Pasikowska found that parents' gender attitudes affect on child's behavior and attitudes toward different spheres of life [1] . Our study helped to show that parents have different attitudes towards boys' and girls' gender behavior strictness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratkowska-Pasikowska found that parents' gender attitudes affect on child's behavior and attitudes toward different spheres of life [1] . Our study helped to show that parents have different attitudes towards boys' and girls' gender behavior strictness.…”
Section: Discussionmentioning
confidence: 99%
“…Adults' social attitudes toward a child's behavior affect not only the child's behavior as well, but also his or her attitudes toward different spheres of life [1][2][3] and even mental health [4][5][6] . The preschool period is characterized by a child's exposure to parental influence.…”
Section: Introductionmentioning
confidence: 99%